Editorial Note - Nzaka Munga, Prof. Cosmas (Multidisciplinary Journal of Technical University of Mombasa, 2024)
We would like to thank all our authors and co-authors who contributed to the  successful release  of this 2nd Issue of MJTUM Volume 3. This issue has a total of 3 original scientific research articles and 3 review articles from a diverse array of fields ranging from application of artificial intelligence tools in education, biotechnology, application of critical and creative thinking in social sciences, and assessment of organizational performance of PWDs in selected institutions in Kenya. The content of all the articles is as a result of dedicated research works from the authors and co-authors. MJTUM is hereby providing a platform to share the contents of these research works in contributing to knowledge dissemination to the scientific community and to all students in their quest to advance knowledge in their respective fields. MJTUM will continue to provide a platform for dissemination of high quality scientific findings to the scientific community. It is my sincere hope that you will enjoy reading the wide coverage of these published articles covered in this issue as we prepare you for the release of Volume 4 of our journal.